Honesty of Larval Begging Signals Covaries With Colony Kin Structure in Formica Ants - Peignier, Mélissa; Pokorny, Tamara; Heinze, Jürgen; Lindgren, Rosanna; Helanterä, Heikki; Schultner, Eva (Frontiers in Ecology and Evolution, 2019)
Social insects live in highly complex societies with efficient communication systems. Begging is one display commonly used by offspring to signal their nutritional state, however begging behavior has received very little attention in social insects. Theory predicts that begging can be either an honest (i.e. honest-signaling strategy) or a dishonest (i.e. scrambling competition) signal of need, with dishonest signals expected to be more likely when relatedness within the group is low. To investigate the presence and honesty of begging, as well as the nature of the involved signals, we used a comparative approach with four species of the ant genus Formica known to differ in the degree of intra-colony relatedness. We investigated the behavior of starved and non-starved larvae of F. aquilonia, F. pressilabris (both low intra-colony relatedness), F. exsecta (intermediate relatedness), and F. fusca (high relatedness). In addition, we assessed the attraction of conspecific workers towards odors extracted from these two classes of larvae and analyzed the larval cuticular hydrocarbon profiles. We found that in F. fusca and F. exsecta, larvae signaled significantly more when starved. In contrast, larvae of F. aquilonia signaled significantly more when they were non-starved, while there was no significant difference in the behavior of starved versus non-starved larvae in F. pressilabris. Our results show that workers were not preferentially attracted to the odor of starved larvae, and we also did not detect any differences between the cuticular hydrocarbon profiles of starved and non-starved larvae. Overall, this study demonstrates among species variation in larval hunger signaling in Formica ants, and encourage further studies for confirming the link between kin structure variation and the honesty of begging signals.